Improving the Effectiveness of Bank Credit Mechanisms in the Development of Industrial Enterprises (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article scientifically examines the directions for improving the efficiency of bank loans in the development of industrial enterprises. Within the framework of the ongoing economic reforms in the country, the study analyzes the role of commercial banks in financing the real sector, the importance of loans provided to industrial enterprises, and the key factors ensuring their effectiveness. Particular attention is paid to issues of risk management in the optimal allocation of credit resources, improvement of collateral requirements, and the introduction of modern approaches to investment project evaluation.Based on the research results, it is substantiated that the development of comprehensive financial mechanisms and practical tools is necessary to enhance the efficiency of bank loans in industrial modernization, production expansion, and the implementation of innovative technologies. Furthermore, relying on international experience, the article provides practical recommendations for improving the quality indicators of lending within the national banking system.